2015
DOI: 10.1007/s00167-015-3784-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of platelet-rich plasma injection for treatment of osteoarthritis of the knee

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 33 publications
2
75
0
3
Order By: Relevance
“…As the CI included 0, we are not able to say PRP is more effective than HA on relieving WOMAC pain and increasing physical function. In this case, the conclusions drawn from the two approaches are contradicting, but our findings were similar to another recent meta-analysis by Kanchanatawan et al 7 They reported that PRP injections had no significant differences in improving WOMAC pain and function scores when compared to HA injections, but had improved functional outcomes in WOMAC total scores, International Knee Documentation Committee (IKDC) score and EuroQol visual analogue scale (EQ-VAS), also suggesting that PRP injections were more efficacious than HA in reducing symptoms, and improving function and quality of life.…”
supporting
confidence: 78%
“…As the CI included 0, we are not able to say PRP is more effective than HA on relieving WOMAC pain and increasing physical function. In this case, the conclusions drawn from the two approaches are contradicting, but our findings were similar to another recent meta-analysis by Kanchanatawan et al 7 They reported that PRP injections had no significant differences in improving WOMAC pain and function scores when compared to HA injections, but had improved functional outcomes in WOMAC total scores, International Knee Documentation Committee (IKDC) score and EuroQol visual analogue scale (EQ-VAS), also suggesting that PRP injections were more efficacious than HA in reducing symptoms, and improving function and quality of life.…”
supporting
confidence: 78%
“…Nonetheless, most comparisons included only 1 or 2 studies due to the small number of RCTs pooled for analysis. Another review included 9 RCTs and synthesized the WOMAC pain subscores and physical function subscores to compare the efficacy of PRP with control [23]. Due to the varied follow-up among studies, synthesis of the data at the latest follow-up might not reflect the changes of PRP efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 145 titles and abstracts were preliminarily reviewed, and 10 published systematic reviews ultimately met the eligibility criteria (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Table presents the methodological characteristics of included systematic reviews. Half of the included systematic reviews only included randomized clinical trials (RCTs), while others included RCTs and non‐RCTs. The evidence degree of each systematic review was Level II.…”
Section: Resultsmentioning
confidence: 99%